Secret Recipe Subang Perdana Kitchen Inventory Management System / Izrul Hazziq Shamsul Anuar - Shamsul Anuar, Izrul Hazziq (2021)
Kitchen Inventory Management is a system that developed to solve the problem faced by Secret Recipe Subang Perdana to improve the flow in managing the inventory process. There are two (2) problems faced by Secret Recipe Subang Perdana based on information obtained from the interview session. The first problem is tedious process to calculating stock manually. Secret Recipe Subang Perdana currently use stock book to manage their inventory and every product need to be calculated manually during closing. Lastly, the process of managing the product quality is inefficient. Secret Recipe Subang Perdana use sticker to label each container for product which the sticker has information of the product. The problems arise when the sticker tear off and the information of product such as the expiry date of product on the container will be gone. The proposed solution to overcome this problem is to develop the Kitchen Inventory Management System that will manage the stock in the inventory and improve the efficiency process of managing the product quality. Modified Waterfall Model is the methodology that have been used to develop Kitchen Inventory Management System which have three (3) phases to achieved three (3) objectives. Firstly, the requirement analysis phase which the objective is to gather and analyze the requirements and the deliverables have been documented in Software requirement Specification (SRS). Secondly, the design phase which the objective is to design a Kitchen Inventory Management System based on gathered and analyzed requirements and the deliverables have been documented in Software Design Document (SDD). The last phase is the implementation which the objectives is to develop the Kitchen Inventory Management System for Secret Recipe Subang Perdana and the deliverables is the system itself. These three (3) objectives have been achieved by following the phase with planned activities. However, there is few recommendations to improve the system where the feature of receive order can be removed and use scanner and barcode to scan the product during checkout. This will be the new way to inventory of the Kitchen Inventory Management System manage other than that , Kitchen Inventory Management System can be integrated with Synergy Ordering System. This will make the kitchen leader able to make ordering to factory when the stock is running low with using only one system. Lastly, by integrating the Kitchen Inventory Manage ment System with point of sale system of Secret Recipe Subang Perdana. By doing this, kitchen leader no need to use receive order feature in system because the product quantity will automatically update when the waiter places an order in the system.